ANALYSIS ENGLISH FIGURATIVE LANGUAGE IN NOVEL â€œLITTLE MENâ€ BY LOUISA MAY ALCOTT - Arsyani, Fatma; Rufinus, Albert; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The research was conducted to find and analyze figurative language (metaphor and simile) in â€œLittle Menâ€, a classic novel by Louisa May Alcott. The research used descriptive qualitative method, which sample was twenty figurative languages taken using random purposeful sampling. Procedure of analysis were 1st reading entire text, 2nd determining tenor and vehicle of figurative language using Richard approach, 3rd describing meanings, 4th describing character education in the novel. The research identified 121 figurative languages, consist of 33,06% metaphors and 66.94% similes. It means the novel uses more simile rather than metaphor, and implies that explicit and direct comparison is frequently found. Most vehicles used ancient figures like Spartan, Colossus of Rhodes; nature and animal life; things; fairy tale Goldilocks and the historical social life. Besides, figurative language together with fictionâ€™ elements, delivers character values:religious,social care,and intelligence. Â  Keywords: figurative language, meaning, character education Â  Abstrak: Penelitian ini bertujuan untuk menemukan dan menganalisa bahasa kiasan (metafora dan persamaan atau simile) dalam novel klasik â€œLittle Menâ€ karya Louisa May Alcott. Penelitian ini menggunakan metode deskriptif kualitatif dengan penarikan sampel secara random purposeful sampling dan diperoleh dua puluh bahasa kiasan. Prosedur analisa data yaitu 1. Membaca keseluruhan teks, 2. Mementukan tenor dan wahana dari bahasa kiasan menggunakan pendekatan Richard, 3. Menjabarkan makna, 4. Menjabarkan pendidikan karakter di novel. Penelitian ini mengidentifikasi 121 bahasa kiasan terdiri dari 33,06% metafora dan 66,94% simile. Novel ini lebih banyak menggunakan simile daripada metafora, hal ini bermakna perbandingan yang sering ditemui adalah perbandingan secara jelas dan langsung. Lazimnya, wahana menggunakan figur kuno, seperti Spartan, Colossus of Rhodes; kehidupan alam dan hewan, benda-benda, cerita dongeng Goldilocks, dan sejarah keidupan sosial. Selain itu, bahasa kiasan bersama elemen-elemen lain di fiksi, menghantar nilai-nilai karakter: taat beragama, peduli sosial, danÂ  intelegensia. Â  Kata Kunci: bahasa kiasan, makna, pendidikan karakter